Diagnostic Yield of Combined Pulmonary Cryobiopsies and Electromagnetic Navigation in Small Pulmonary Nodules - Taton, Olivier; Bondue, Benjamin; Gevenois, Pierre Alain; Remmelink, Myriam; Leduc, Dimitri (Pulmonary Medicine, 2018)
Background. An increasing number of pulmonary nodules of unknown nature are detected as a result of screening by CT in high lung cancer risk patients. Objectives. The purposes of this study were to assess the diagnostic yield of electromagnetic navigation bronchoscopy (ENB) combined with transbronchial lung cryobiopsy (TBLC) and to compare it with standard transbronchial biopsy (TBB) in pulmonary nodules of less than 2 cm in diameter. Methods. We prospectively included 32 patients (18 men and 14 women, mean age 68 ± 9 years) with nodules of less than 2 cm in diameter and no metastasis at 18FDG PET-CT. The nodule position was determined by ENB, radial endobronchial ultrasonography miniprobe, and fluoroscopy. Eight samples were obtained, six by TBB and two by TBLC. Results. Nodule diameter averaged 16 ± 3 mm. Twenty-five nodules were malignant and 18 were surgically resected. Surgery was avoided in four patients as the biopsies revealed a benign disease. The samples obtained by TBLC were five times larger than those by TBB. The diagnostic yields of TBLC and TBB were 69% and 38%, respectively (p=0.017). Adverse events consisted in 15 mild or moderate bleedings and one pneumothorax. Conclusions. In the setting of peripheral pulmonary lesions of less than 20 mm in diameter, ENB-combined TBLC is feasible and safe, provides larger samples, and has higher diagnostic yield than TBB.